Genome-wide reprogramming of primary and secondary metabolism, protein synthesis, cellular growth processes, and the regulatory infrastructure of Arabidopsis in response to nitrogen - Scheible, W.R; Morcuende, R; Czechowski, T; Fritz, C; Osuna, D; Palacios-Rojas, N; Schindelasch, D; Thimm, O; Udvardi, M.K; Stitt, M (Plant physiology (Bethesda), 2004)
Transcriptome analysis, using Affymetrix ATH1 arrays and a real-time reverse transcription-PCR platform for >1,400 transcription factors, was performed to identify processes affected by long-term nitrogen-deprivation or short-term nitrate nutrition in Arabidopsis. Two days of nitrogen deprivation led to coordinate repression of the majority of the genes assigned to photosynthesis, chlorophyll synthesis, plastid protein synthesis, induction of many genes for secondary metabolism, and reprogramming of mitochondrial electron transport. Nitrate readdition led to rapid, widespread, and coordinated changes. Multiple genes for the uptake and reduction of nitrate, the generation of reducing equivalents, and organic acid skeletons were induced within 30 min, before primary metabolites changed significantly. By 3 h, most genes assigned to amino acid and nucleotide biosynthesis and scavenging were induced, while most genes assigned to amino acid and nucleotide breakdown were repressed. There was coordinate induction of many genes assigned to RNA synthesis and processing and most of the genes assigned to amino acid activation and protein synthesis. Although amino acids involved in central metabolism increased, minor amino acids decreased, providing independent evidence for the activation of protein synthesis. Specific genes encoding expansin and tonoplast intrinsic proteins were induced, indicating activation of cell expansion and growth in response to nitrate nutrition. There were rapid responses in the expression of many genes potentially involved in regulation, including genes for trehalose metabolism and hormone metabolism, protein kinases and phosphatases, receptor kinases, and transcription factors.